Information and Communication Technology (ICT) in English Language Teaching - Gusti Nur Hafifah (Universitas Muhammadiyah Surabaya, 2019)
ICT has been a basic requirement and essential aspect of education in global context nowadays. ICT in the form of digital literacy becomes one of the skills that students must acquire besides words and numerical literacy in the 21st era of learning. This paper explores the progress of ICT integration in education, especially in English Language Teaching. It reviews several findings from empiric studies about the impact of ICT toward teaching and learning. It elaborates the chronological development of ICT in ELT starting from; CALL, TELL, LMS, and how it is integrated into Blended learning. Teachersâ€™ perspective of ICT is also discussed to see how it affects ICT practices. At last, it expounds the recent research result of the implementation of ICT in the teaching of English in Indonesia.Â Keyword: ICT, ELT, teachersâ€™ perspective, Indonesia